Impact des aménagements de conservation des eaux et des sols sur la régénération des ressources ligneuses en zone sahélienne et nord soudanienne du Burkina Faso - Souleymane Ganaba (VertigO)
The aim is to study the impact of soil and water conservation management (SWC) technologies in degraded land recuperation in Sahelian zone. Six agro-pastoral units of project intervention zone are composed with 2 in north sudanian zone (Boundoré and Kabo-Gountouré) and 4 in sahelian zone (Dori North, Falagountou, Korea and Sampelga. A floristic inventory was used to evaluate soil and water management impact on biodiversity in16 pastoral plots and their controls composed by 5 pastorals and 11 cultivated of 1 ha.SWC management favoured the woody and herbaceous vegetation reconstitution. Cassia obtusifolia settled inside the micro-basins of half-moon, surroundings the stones bounds and filter dikes competing with others plants specially the woody plants. The half-moons and the stones bounds, the filter dikes and ‘sous-solage’ and ‘scarifiage’    favoured the settlement and development of perennial vegetation constituted by Acacia nilotica,  Acacia tortilis, Balanites aegyptiaca, Leptadenia hastata, Ziziphus mauritiana. The half moons management gave the best results on density and floristic composition. The survival level of woody plant regeneration in 1999 is 9, 45% in pastoral plots and 2,65% in cultivated plots. The most resistant species having survived from 1999 were Balanites aegyptiaca, Acacia tortilis and Acacia senegal. These plants are been fodder and multipurpose trees. Good management of  managed lands is necessary to restore sustainable resources.